Social responsibility and sustainability : multidisciplinary perspectives through service learning - McDonald, Tracy, 1956- (Service learning for civic engagement series., 2011)
This concluding volume in the series presents the work of faculty who have been moved to make sustainability the focus of their work, and to use service learning as one method of teaching sustainability to their students. The opening section of this book offers models for opening students to the awareness of the ecological aspects of sustainability, and of the interdependence of the ecosystem with human decisions and behavior. Part II explores means for fostering commitment to community service and experiencing the capacity to effect change. Part III addresses sustainability within the busines.